Patterns of spousal accommodation and conflict in traditional and modern farm families - Hannan, Damian (Economic & Social Studies, 1978)
This paper reports the results of interviews with a random sample of 408 couples operating family farms in the West of Ireland. Attention is focused on the extent of consensus on values between husbands and wives, the process of accommodation to each other's values, as well as some of the bases of conflict of values that occurs as families modernise. In the light of these results, the relative validity and utility of a number of theoretical orientations in family sociology are assessed.
Keywords: Family farms - Ireland; Agriculture - Sociology